Mechanisms and comfort optimization of human–vehicle–bridge coupled vibrations in separated-layer bridges - Tailei Chen; Liming Zhu; Shiling Xing; Zhiwei Xu; Zhenkang Hua (Engineering Structures, 2026)

Cyclic response of severely damaged subway station central columns repaired with ECC jackets under highly variable axial loads - Jia Yang; Peng Deng; Chao Zhang; Renpeng Chen; Shiling Pei (Engineering Structures, 2026)

A low-cost solar disinfection platform: hydrogel-encapsulated benzyl frameworks for continuous in situ H2O2-driven water treatment - Wenjuan Zhang; Lizheng Chen; Xiaojuan Zhao; Shiling Zhang; Chongling Cheng; Juan Du; Kaikai Ba; Bo Wang; Tengfeng Xie; Xuefeng Chu; Gang Liu; Dayang Wang (Water Research, 2026)

Pickering emulsions stabilized by bovine bone gelatin - xanthan gum conjugates: an effective carrier for curcumin encapsulation - Mingfeng Sun; Wenxia Wu; Huanhuan Yang; Mou Zhao; Xiang Zhou; Nengmao Chen; Jingtao Sun; Shiling Lu; Qingling Wang; Juan Dong (Food and Bioproducts Processing, 2026)

Autophagy attenuates the secondary senescence of endometrial stromal cells induced by Bisphenol S - Xuguang Mi; Jianhua Fu; Lei Liu; Lingshan Wang; Shiling Chen; Mengxue Wu; Chunxue Niu; Yan Wang; Lixin Cao; Lin Wang; Ling Deng; Xiaodan Lu; et al. (Chemico-Biological Interactions, 2026)

Cerium-iron symbiotic nanozyme alleviates drought stress in wheat by targeting stomatal regulation and photosynthesis - Keyu Chen; Xiaowei Wang; Tao Yuan; Gehong Su; Chun Wu; Mengmeng Sun; Yanying Wang; Ming Hao; Xue Chen; Shiling Feng; Fuyong Wu; Dengcai Liu; et al. (Bioresource Technology, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Exploring the Interconnections Between Mitochondrial Dysfunction and Polycystic Ovary Syndrome: A Comprehensive Integrated Analysis - Suqin Zhang; Mingyue Zhu; Shiling Chen (Biochemical Genetics, 2026)

Seismic fragility of segmental tunnels with optimal pairs of intensity measure and engineering demand parameter - Jiaxing Zhou; Zihan Yang; Chao Zhang; Zhixiong Lang; Peng Deng; Ze Chen; Shiling Pei; Renpeng Chen (Soil Dynamics and Earthquake Engineering, 2026)

Ultrasound-assisted phosphorylation-modified sunflower meal protein: characterization and evaluation as a polyphenol delivery system - Zeliang Qi; Jiaxin Jin; Haojuan Chen; Jinsong He; Yazhi Liu; Haotian Cui; Yi Yang; Shiling Lu; Juan Dong; Qingling Wang (Journal of Food Engineering, 2026)

Impact of ultrasound-assisted braising on Xinjiang-style jar stewed mutton flavor compounds - Xinyu Chen; Tengbin Wang; Huabo Fu; Siqi Qiu; Yuhan Duan; Xulong Li; Jingyun Wang; Xin Guo; Shiling Lu (Food Chemistry, 2026)

Preparation and characterization of modified sunflower meal protein–quercetin nanoparticles: Shelf–life study of seasoned lamb kebabs - Jinsong He; Jiaxin Jin; Haojuan Chen; Zeliang Qi; jinling Wang; Xiaomeng Wei; Yi Yang; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2026)

Enhanced degradation of carbamazepine in water by a chitosan-supported tea polyphenols/nano-zero-valent iron system: Mechanistic insights and toxicological risk assessment - Weiwei Yu; Yuanxin Liu; Jianglin Tan; Yue Liang; Jiang Hu; Qing Tu; Shuo Yang; Ji Li; Sikai Zhao; Yang Liu; Xinyan Li; Yan Luo; et al. (Journal of Cleaner Production, 2025)

Highly efficient degradation of sulfamethoxazole by peroxydisulfate activated with phosphoric acid-modified biochar-supported copper sulfide: Performance, mechanisms, and potential applications - Weiwei Yu; Xiyin Zheng; Xi Chen; Cong Liu; Bolin Li; Lu Lv; Yuanxin Liu; Ji Li; Xinyan Li; Yan Luo; Dan Liu; Shiling Chen (Journal of Environmental Chemical Engineering, 2025)

Dialysis-assisted control significantly enables stable long-term unaerated partial nitrification in a microalgal-bacterial consortium treating hydrolyzed urine - Zimu Li; Zhipeng Chen; Yue Xie; Yanbing Hu; Shiling Xu; Sheng Yu; Shuang Qiu; Shijian Ge (Bioresource Technology, 2025)

Vegetation dynamics and carbon isotope responses to the early eocene hyperthermals - Peizong Lü; Zuoling Chen; Yongli Lu; Shiling Yang; Zihua Tang; Zhongli Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Human umbilical cord mesenchymal stem cell-derived exosomes repair raloxifene-induced damage in endometrial stromal cells via autophagy activation - Shiling Chen; Xiuying Lin; Lei Liu; Jianhua Fu; Xiaodan Lu; Chunxue Niu; Qilai Wang; HaiFeng Wei; Mengxue Wu; Munan Sun; Lixin Cao; Xuguang Mi; et al. (Reproductive Toxicology, 2025)

Study of changes in volatile flavor substances during the processing and storage of mutton ham - Xinyu Chen; Huabo Fu; Siqi Qiu; Yuhan Duan; Xulong Li; Xin Guo; Shiling Lu; Jingyun Wang (Food Research International, 2025)

Physiological and genetic responses of Chlorella sp. to nitrite accumulation in microalgal-bacterial consortium with partial nitrification treating municipal wastewater - Mengting Li; Zhipeng Chen; Xiang Li; Sheng Yu; Shiling Xu; Shuang Qiu; Shijian Ge (Water Research, 2025)

Characterization of ultrasound-induced soybean peptide particles (SPPs) and SPP-stabilized Pickering emulsions combined with amino acid sequence analysis - Ping Han; Mou Zhao; Zhouping Wang; Nengmao Chen; Fuguo Liu; Shiling Lu; Juan Dong; Jingtao Sun (Food Hydrocolloids, 2025)

Correcting microplastic pollution and risk assessment in Chinese watersheds - Feng Yu; Weiwei Yu; Yan Zhao; Yue Liang; Jiang Hu; Rongqi Liu; Shiling Chen; Qinwei Chen; Yuanxin Liu; Xiyin Zheng; Xinyan Li (Environmental Pollution, 2025)

Evolving Therapeutic Landscape of Intracerebral Hemorrhage: Emerging Cutting-Edge Advancements in Surgical Robots, Regenerative Medicine, and Neurorehabilitation Techniques - Danyang Chen; Zhixian Zhao; Shenglun Zhang; Shiling Chen; Xuan Wu; Jian Shi; Na Liu; Chao Pan; Yingxin Tang; Cai Meng; Xingwei Zhao; Bo Tao; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the most serious form of stroke and has limited available therapeutic options. As knowledge on ICH rapidly develops, cutting-edge techniques in the fields of surgical robots, regenerative medicine, and neurorehabilitation may revolutionize ICH treatment. However, these new advances still must be translated into clinical practice. In this review, we examined several emerging therapeutic strategies and their major challenges in managing ICH, with a particular focus on innovative therapies involving robot-assisted minimally invasive surgery, stem cell transplantation, in situ neuronal reprogramming, and brain-computer interfaces. Despite the limited expansion of the drug armamentarium for ICH over the past few decades, the judicious selection of more efficacious therapeutic modalities and the exploration of multimodal combination therapies represent opportunities to improve patient prognoses after ICH.

Deep learning model based on coupled SWAT and interpretable methods for water quality prediction under the influence of non-point source pollution - Juan Huan; Yixiong Fan; Xiangen Xu; Liwan Zhou; Hao Zhang; Chen Zhang; Qucheng Hu; Wenxin Cai; Haoran Ju; Shiling Gu (Computers and Electronics in Agriculture, 2025)

Volatile profiles and characteristic odorants in camellia seeds with different heat pretreatments - Shiling Feng; Pingjin Li; Yusong Li; Xinsheng Xiao; Xinyu Chen; Haiqin Leng; Heng Liang; Lijun Zhou; Tao Chen; Chunbang Ding (Food Chemistry, 2025)

Recycling of flotation residual carbon from coal gasification fine slag through thermal combustion reaction: Insight into the spatial and temporal multi-scale evolution of typical heavy metals - Yang Guo; Jianjun Wu; Fanhui Guo; Yixin Zhang; Shiling Yuan; Chunan Du; Juan Chen; Meng Lin (Fuel, 2025)

Development and characterization of wax–bovine bone protein-grapeseed oil composite oleogels: Experimental and molecular simulation studies - Jingya Chen; Wenjing Shi; Cenchen Ran; Haotian Cui; Yangyang Li; Kui Diao; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

MicroRNA-451 Regulates Angiogenesis in Intracerebral Hemorrhage by Targeting Macrophage Migration Inhibitory Factor - Shuang Bai; Ge Zhang; Shiling Chen; Xuan Wu; Jiarui Li; Jingxuan Wang; Danyang Chen; Xia Liu; Jiahui Wang; Yuanwei Li; Yingxin Tang; Zhouping Tang (Molecular Neurobiology, 2024)
Intracerebral hemorrhage (ICH) is a subtype of stroke with the highest fatality and disability rate. Up to now, commonly used first-line therapies have limited value in improving prognosis. Angiogenesis is essential to neurological recovery after ICH. Recent studies have shown that microRNA-451(miR-451) plays an important role in angiogenesis by regulating the function of vascular endothelial cells. We found miR-451 was significantly decreased in the peripheral blood of ICH patients in the acute stage. Based on the clinical findings, we conducted this study to investigate the potential regulatory effect of miR-451 on angiogenesis after ICH. The expression of miR-451 in ICH mouse model and in a hemin toxicity model of human brain microvascular endothelial cells (hBMECs) was decreased the same as in ICH patients. MiR-451 negatively regulated the proliferation, migration, and tube formation of hBMECs in vitro . MiR-451 negatively regulated the microvessel density in the perihematoma tissue and affected neural functional recovery of ICH mouse model. Knockdown of miR-451 could recovered tight junction and protect the integrity of blood-brain barrier after ICH. Based on bioinformatic programs, macrophage migration inhibitory factor (MIF) was predicted to be the target gene and identified to be regulated by miR-451 inhibiting the protein translation. And p-AKT and p-ERK were verified to be downstream of MIF in angiogenesis. These results all suggest that miR-451 will be a potential target for regulating angiogenesis in ICH.

Assessing the structural and foaming property changes in egg yolk proteins due to malondialdehyde: Experimental and molecular docking studies - Jingya Chen; Jiaxin Jin; Yu Liu; Mengbin Zhao; Zeliang Qi; Wenjing Shi; Yangyang Li; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

Extraction and identification of polyphenol from Camellia oleifera leaves using tailor-made deep eutectic solvents based on COSMO-RS design - Shiling Feng; Guanfeng Deng; Huanyao Liu; Haiqiu Shi; Pingjin Li; Xiao Li; Tao Chen; Lijun Zhou; Ming Yuan; Chunbang Ding (Food Chemistry, 2024)

Pliocene CO2 rise due to sea-level fall as a mechanism for the delayed ice age - Shiling Yang; Yongda Wang; Xiaofang Huang; Minmin Sun; Jingtai Han; Xu Wang; Zuoling Chen; Shihao Zhang; Wenying Jiang; Zihua Tang; Zhaoyan Gu; Shangfa Xiong; et al. (Global and Planetary Change, 2024)

Coagulation pretreatment coupled with indigenous microalgal-bacterial consortium system for on-site treatment of rural black wastewater - Mengting Li; Zhipeng Chen; Di Zhou; Shiling Xu; Shuang Qiu; Shijian Ge (Science of The Total Environment, 2024)

Correction to: Effects of Dl-3‑n‑butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of Dl-3-n-butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Vascular cognitive impairment (VCI) has been one of the major types of cognitive impairment. Blood–brain barrier damage plays an essential part in the pathogenesis of VCI. At present, the treatment of VCI is mainly focused on prevention, with no drug clinically approved for the treatment of VCI. This study aimed to investigate the effects of DL-3-n-butylphthalide (NBP) on VCI rats. A modified bilateral common carotid artery occlusion (mBCCAO) model was applied to mimic VCI. The feasibility of the mBCCAO model was verified by laser Doppler, 13 N-Ammonia-Positron Emission Computed Tomography (PET), and Morris Water Maze. Subsequently, the Morris water maze experiment, Evans blue staining, and western blot of tight junction protein were performed to evaluate the effect of different doses of NBP (40 mg/kg, 80 mg/kg) on the improvement of cognitive impairment and BBB disruption induced by mBCCAO. Immunofluorescence was employed to examine the changes in pericyte coverage in the mBCCAO model and the effect of NBP on pericyte coverage was preliminarily explored. mBCCAO surgery led to obvious cognitive impairment and the decrease of whole cerebral blood flow, among which the blood flow in the cortex, hippocampus and thalamus brain regions decreased more significantly. High-dose NBP (80 mg/kg) improved long-term cognitive function in mBCCAO rats, alleviated Evans blue leakage and reduced the loss of tight junction proteins (ZO-1, Claudin-5) in the early course of the disease, thereby exerting a protective effect on the blood–brain barrier. No significant changes in pericyte coverage were observed after mBCCAO. High-dose NBP improved cognitive function in mBCCAO rats. High-dose NBP protected the integrity of BBB by upregulating TJ protein expression, rather than regulating pericyte coverage ratio. NBP could be a potential drug for the treatment of VCI.

Isolation and characterization of an endophytic fungi from Zingiber officinale Rosc. and its activity to promote the growth of tissue culture ginger plantlets in bottles - Shuting Zhang; Yinghong Pei; Jiao Wang; Xiaolong Lin; Zizhong Tang; Lijun Zhou; Tao Chen; Shiling Feng; Chunbang Ding; Yanger Chen; Zhongwei Zhang; Shu Yuan; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Freshwater ecosystem collapse and mass mortalities at the Paleocene-Eocene thermal maximum - Zuoling Chen; Zhongli Ding; Jimin Sun; Shiling Yang; Xijun Ni; Xu Wang; Yongli Wang; Jiangyong Zhang; Wei He (Global and Planetary Change, 2023)

Effects of fabrication of conjugates between different polyphenols and bovine bone proteins on their structural and functional properties - Li Pan; Jingya Chen; Huihui Fu; Niannian Wang; Junrong Zhou; Shuyao Zhang; Shiling Lu; Juan Dong; Qingling Wang; Haiyan Yan (Food Bioscience, 2023)

A novel Stauntonia leucantha fruits arabinogalactan: isolation and structural characterization - Hui Li; Tao Gao; Zhonghao Zhang; Jiangping Lei; Junchao Hu; Zizhong Tang; Shiling Feng; Chunbang Ding; Tao Chen; Yanger Chen; Shu Yuan; Ming Yuan (Carbohydrate Polymers, 2023)

Total organic carbon content as an early warning indicator of soil degradation - Licheng Guo; Shangfa Xiong; Yulu Chen; Jingyi Cui; Shiling Yang; Heng Wang; Yongda Wang; Zhongli Ding (Science Bulletin, 2023)

Changes in Cerebral Blood Flow and Diffusion-Weighted Imaging Lesions After Intracerebral Hemorrhage - Jingfei Yang; Jie Jing; Shiling Chen; Xia Liu; Yingxin Tang; Chao Pan; Zhouping Tang (Translational Stroke Research, 2022)

Large‐scale synoptic atmospheric moisture circulation patterns associated with variability of daily precipitation over East China - Bingjun Liu; Shiling Chen; Xuezhi Tan (International Journal of Climatology, 2021)
This study identifies the variability of large‐scale atmospheric patterns (LSMPs) and atmospheric moisture circulation patterns associated with the variability of daily precipitation over East China using the self‐organizing maps (SOM) method. The spatiotemporal characteristics of the occurrence and intensity of daily precipitation were linked with the variabilities of LSMPs. Results show that the synoptic moisture transport over East China in both dry season and rainy season can be classified into eight patterns, and the occurrence frequency and primary occurring months of the eight patterns are varied. In the dry season, the wetter pattern (the drier pattern) exhibits a significant decreasing (increasing) trend with a slope of −0.23 (0.63)% year −1 at the confidence level of 0.95 during 1979–2018. The LSMPs corresponding to each atmospheric moisture circulation pattern, including the composite mean values of vertically integrated water vapour transport fields, 500 hPa geopotential height (Z500) anomalies and sea surface temperature anomalies (SSTA) in surrounding oceans, indicate that the primary oceanic moisture source of the dry season is western North Pacific (WNP), while that of the rainy season is WNP and the Indian Ocean. The location and intensity variabilities of subtropical high affect the transport and amount of water vapour along with its western flank to arrive in East China. SSTA has an influential link with the regional circulations and convection activity, and thus plays an important role in affecting water vapour transport.

Inconsistent changes in global precipitation seasonality in seven precipitation datasets - Xuezhi Tan; Yi Wu; Bingjun Liu; Shiling Chen (Climate Dynamics, 2020)

The differentiation of iron-reducing bacterial community and iron-reduction activity between riverine and marine sediments in the Yellow River estuary - Hongxia Zhang; Fanghua Liu; Shiling Zheng; Lei Chen; Xiaoli Zhang; Jun Gong (Marine Life Science & Technology, 2020)

Inter-comparison of spatiotemporal features of precipitation extremes within six daily precipitation products - Shiling Chen; Bingjun Liu; Xuezhi Tan; Yi Wu (Climate Dynamics, 2020)

Characteristics and circulation background of extreme precipitation over East China - Shiling Chen; Bingjun Liu; Xuezhi Tan; Zeqin Huang (Natural Hazards, 2019)